Pengaruh dukungan sosial dan parenting self-efficacy terhadap parental burnout pada ibu bekerja - Muliasari, Ainun; Amalia, Sofa (Cognicia, 2024)
Nowadays becoming parents is not a simple thing, especially as a mother. In this era, there are many demands that make mothers carry out a dual role, a housewife and a working mother. Therefore, the multiple roles chosen by the mother will cause burnout and have an impact for childcare. The purpose of this study is to determine the effect of social support and parenting self-efficacy on parental burnout in working mothers. This research uses a quantitative approach and a non-experimental quantitative research design with a causal relationship. The study encompassed a cohort of one hundred and twelve (112) employed mothers within governmental or private organizations, chosen through the application of accidental sampling methodology. The data analysis with a simple linear regression test to measure the effect of social support on parental burnout (r= 0,403, p < 0,05) and parenting self-efficacy on parental burnout (r=0,471, p <0,05) and multiple linear regression test to measure the effect of social support and parenting self-efficacy on parental burnout (p < 0,05). Social support makes an effective contribution to parental burnout of seven point seven percent (7,7%) and parenting self-efficacy of seventeen point six percent (17,6%).